2016
DOI: 10.1177/0886260516682520
|View full text |Cite
|
Sign up to set email alerts
|

Beaten Into Submissiveness? An Investigation Into the Protective Strategies Used by Survivors of Domestic Abuse

Abstract: The aim of the study was to identify the prevalence and perceived helpfulness of a variety of protective strategies that were used by female survivors of domestic abuse and to explore factors that may have influenced strategy usage. Forty participants were recruited from a voluntary sector domestic abuse service, commissioned by an outer London local authority in the United Kingdom, in early 2014. The measurement tools used were the Intimate Partner Violence Strategies Index (IPVSI) and the Coordinated Action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…staying with friends/family). In a recent study by Irving and Liu (2016), female IPV victims were reported to use many different strategies to protect themselves from future IPV. Placating strategies were used the most and were considered helpful by many of the victims.…”
Section: Victim Strategiesmentioning
confidence: 99%
“…staying with friends/family). In a recent study by Irving and Liu (2016), female IPV victims were reported to use many different strategies to protect themselves from future IPV. Placating strategies were used the most and were considered helpful by many of the victims.…”
Section: Victim Strategiesmentioning
confidence: 99%
“…Using constant comparison 16 , transcripts were compared within and between each other, aiding the iterative search for themes which were then reviewed, defined and named. As well as using this inductive and iterative approach, the analysis was rooted in a theoretical framework derived from the literature on the female experience of DA 2,3,[17][18][19][20][21][22][23][24] , DA among females from higher socioeconomic groups 25 and literature regarding necessity of specialised services for doctors with mental health problems [26][27][28][29] . Disconfirming cases were sought to further develop the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to IPV, this suggests everyday peace could provide a framework to understand the behaviours and agency of women who choose to stay in abusive relationships (or who are navigating post-separation relationships), and through understanding, point to ways to support them beneath the macro policy approaches of government and formalised programs typically provided in the family violence space. Additionally, practices of everyday peace could be presented as a soft-entry point for people unwilling to engage with traditional family violence supports, as it works with people at the stage they are at rather than pushing them to make significant decisions which they may be unready or unable to enact-particularly noting the complexity and heightened risk level associated with terminating a violent relationship (Irving & Chi-pun Liu, 2020;Fisher & Stylianou, 2019). In doing this, everyday peace accepts women as they are and respects the agency with which they live their lives.…”
Section: Blame Deferringmentioning
confidence: 99%
“…Practices identified in the everyday peace literature best correlate with what are termed placating strategies in the family violence literature. IPV research suggests these comprise over 80 percent of the strategies adopted by women addressing violence (Irving & Chi-pun Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%